Entropy generation in MHD Maxwell nanofluid flow with variable thermal conductivity, thermal radiation, slip conditions, and heat source - Asim Aziz; Moniba Shams (AIP Advances, 2020)
It is important to study heat transfer processes due to fluid flow in the context of entropy because the efficiency of such systems depends on reduction in entropy generation. Moreover, there is a need to develop mechanisms to control entropy generation in thermal systems. In this work, we study volumetric entropy generation rate in electrically conducting Maxwell nanofluid over a penetrable stretching sheet with variable thermal conductivity, velocity slip conditions, thermal radiation, and internal heat source effect. The governing equations of flow, heat transfer, and entropy generation have been abridged under the suppositions of boundary layer approximations and low Reynolds numbers. Solutions to the governing system of partial differential equations are carried out by transforming them into the system of ordinary differential equations using suitable similarity transformations. The resultant system is then solved numerically using a shooting technique along with the fourth order RK method. Numerical computations are carried out for water based Cu-water and Al2O3-water nanofluids. Corporeal topographies of velocity, temperature, entropy generation, Bejan number, skin friction coefficient, and Nusselt number are presented. The impact of important physical parameters are discussed through graphs and tables.